A well-rounded school library extent of compliance to library standards in the collection and services of elite schools in science and the arts - Macasero, Joseph Percival B.; Gonzales, Grace Marie B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2003)
This study focused on the extent of compliance of elite high school libraries' collection and service to standards set by the Department of Education Culture and Sports and feedback based from their users. Elite schools' libraries studied are libraries of schools specializing in sciences and the arts in the Philippines, namely Philippine Science High School and Philippine High School for the Arts. The researcher aimed to determine if the school library of these schools have a well-rounded collection and services that caters to their user who are in a way special because of their intelligence and talents.
Surveys were answered by the users of the two libraries to further strengthen the answers of their librarians to questions asked by the researcher to be able to obtain answers that would make this study significant. Descriptive Statistical Method was used to determine the information materials that users often use, and information materials based on the subjects that they often see in their library. T-test and ANOVA was also used to determine the strength of the collection of each library in science, arts and other subjects. Another ANOVA was used to analyze the satisfaction of the user to the service and efficiency of their library.
The findings show that both school libraries are effective in providing their users with the necessary materials. Both schools have efficient collection in science, arts and other subjects. The analysis also shows that Philippine Science High School gives more attention to their science collection and the Philippine High School for the Arts focuses more in their arts collection but never the less, both schools would give their users the needed information that they need. Indeed, both schools have well rounded libraries based from their collection and services that they offer to their users.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: School libraries -- Philippines -- Quezon City; School libraries -- Philippines -- Laguna; Art libraries -- Philippines -- Laguna; Scientific libraries -- Philippines -- Quezon City